2020
DOI: 10.1016/j.xfre.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index is not associated with donor oocyte recipient success: an ideal study using a paired analysis of sibling-oocytes

Abstract: Objective: To determine whether a higher body mass index (BMI) adversely affects endometrial receptivity. Design: Retrospective cohort study. Setting: Academic medical center. Patient(s): All donor egg recipients (DERs) who received fresh sibling-oocytes (oocytes from a donor that were retrieved from a single controlled ovarian hyperstimulation [COH] cycle and split between two recipients) at our center over a 7-year period were included. Intervention(s): COH of a donor with fresh embryo transfer to recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…We compared 71 pairs of donor oocyte recipients, in which one recipient was normalweight and the other was obese, who received "sibling oocytes" (oocytes from a donor that were retrieved from a single controlled ovarian hyperstimulation cycle and split between the two patients). We observed similar implantation rates and live birth rates between the patient pairs suggesting that obesity does not adversely affect endometrial receptivity [24].…”
Section: Discussionsupporting
confidence: 59%
“…We compared 71 pairs of donor oocyte recipients, in which one recipient was normalweight and the other was obese, who received "sibling oocytes" (oocytes from a donor that were retrieved from a single controlled ovarian hyperstimulation cycle and split between the two patients). We observed similar implantation rates and live birth rates between the patient pairs suggesting that obesity does not adversely affect endometrial receptivity [24].…”
Section: Discussionsupporting
confidence: 59%
“…Body mass index has no effect on donor oocyte recipient achievement [26]. In gestational carriers, CPR, LPR, and MR were not considerably different throughout the BMI categories [27].…”
Section: Impact Of Obesity On the Success Of Ivfmentioning
confidence: 99%
“…16 In a more recent study published in 2020, the authors used a unique shared donor oocyte model to evaluate whether women with discrepant BMIs who received sister oocytes from the same donor oocyte cycle had similar outcomes and found that a higher BMI did not increase miscarriage rates. 17…”
Section: Oocytementioning
confidence: 99%